2013
DOI: 10.1146/annurev-physiol-030212-183754
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin Secretion in Human Pancreatic Islets

Abstract: Pancreatic β cells secrete insulin, the body's only hormone capable of lowering plasma glucose levels. Impaired or insufficient insulin secretion results in diabetes mellitus. The β cell is electrically excitable; in response to an elevation of glucose, it depolarizes and starts generating action potentials. The electrophysiology of mouse β cells and the cell's role in insulin secretion have been extensively investigated. More recently, similar studies have been performed on human β cells. These studies have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
557
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(583 citation statements)
references
References 127 publications
18
557
1
7
Order By: Relevance
“…50,73,74 It has subsequently been shown that supplementation of islets with serum is essential for preserving islet function. 79 Given that human β-cells are known to burst, 75,80-83 and that the Cha-Noma model generates bursting dynamics, we opted to use the Cha-Noma model as a reliable proxy for a human β-cell in our models of human islets. This also afforded a direct comparison of the influence of islet architecture between mouse and human.…”
Section: Discussionmentioning
confidence: 99%
“…50,73,74 It has subsequently been shown that supplementation of islets with serum is essential for preserving islet function. 79 Given that human β-cells are known to burst, 75,80-83 and that the Cha-Noma model generates bursting dynamics, we opted to use the Cha-Noma model as a reliable proxy for a human β-cell in our models of human islets. This also afforded a direct comparison of the influence of islet architecture between mouse and human.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose is metabolized in b-cells, which causes the production of ATP and an increase in the ATP:ADP ratio, resulting in the closure of ATP-sensitive potassium channels (K ATP channels) in the cell membrane and subsequent depolarization of the membrane. The depolarization of cell membranes opens the voltage-gated calcium channel, leading to calcium influx, and the accumulation of calcium triggers the fusion of secretory vesicles to the plasma membrane to release insulin (Layden et al 2010, Rorsman & Braun 2013 subsequently decreases glucose-stimulated insulin secretion (Bordone et al 2006). UCP2 is a direct target of miR-15a in b-cells.…”
Section: Roles Of Mirnas In Diabetes Mirnas and Insulin Releasementioning
confidence: 99%
“…First-phase secretion occurs within ϳ10 min of glucose stimulation as a kinetically defined and transient event, which is then followed by a sustained second-phase during which insulin is secreted for a longer duration but at a reduced rate. Granules released during the second-phase of insulin secretion require recruitment from storage/reserve pools deep within the cell (7,8). It has become apparent that the mobilization of insulin secretory granules from the storage pools to the cell surface requires the dynamic reorganization of the actin cytoskeleton, although the precise molecular events underpinning glucose-induced actin remodeling remain unclear (9 -11).…”
mentioning
confidence: 99%